Performance and carcass traits of heifers Rubia Gallega x Nellore supplemented with chromium picolinate - Moreira, Paulo Sergio Andrade [UNESP]; El Farra, Aymann; Guimarães, Leonardo Virgilio Gregorio; Lorenço, Fabio José; Neto, Angelo Polizel [UNESP]; Palhari, Celina; Berber, Rodolfo Cassimiro Araujo (Lepidus Tecnologia, 2019)
The objective was to evaluate the productive performance and the carcass traits of Nellore (NEL) and Rubia Gallega x Nellore F1 (NRG) heifers, subjected to energy-protein supplementation with chromium picolinate (CrP). Sixty heifers (30 NEL and 30 NRG) with a mean initial adjusted body weight (BW) of 214.50 kg and mean age of 201 days were distributed into a completely randomized design, in a 2 × 2 factorial (2 genetic groups x 2 supplementation groups). The experimental period lasted 320 days. There was no interaction (pp>0.05) between the genetic groups and the supplements. The addition of CrP to the supplement did not alter the performance and carcass characteristics evaluated (pp>0.05). However, the NRG genetic group was better than the NEL in the performance characteristics as final live weight, mean daily gain and carcass yield as carcass yield, Muscularity (p<0.05). The use of the Rubia Gallega genotype in crossbreeding provides an increase in production of heavier carcasses with lower fat percentages and higher yields when compared to the use of Nellore heifers.
Keywords: Crossbreed; Mineral; Muscle growth; Ultrasound